2004
DOI: 10.1021/tx0300535
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxamine:  An Extremely Potent Scavenger of 1,4-Dicarbonyls

Abstract: 1,4-Dicarbonyl compounds, which include 2,5-hexanedione and recently discovered endogenous 4-ketoaldehydes (levuglandins, isoketals, and neuroketals), exhibit severe toxicity. The key step in the toxicity of these compounds is their reaction with the lysyl residues of proteins to form pyrrole adducts. To screen for effective scavengers of these toxic compounds, we determined the reaction rates of pyrrole formation for a series of primary amines with a model 4-ketoaldehyde, 4-oxopentanal (OPA). We found pyridox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 19 publications
4
106
0
Order By: Relevance
“…One of the most promising and selective strategies might be to scavenge these γKA with amine containing compounds that are more reactive than lysyl groups. Previous observations suggested that PM was a good candidate for a γKA scavenger because it reacts with γKAs about 2,000 times faster than does lysine (29). Our present study showed that PM significantly inhibited the formation of lysylIsoK adducts when coincubated with excess lysine and oxidized arachidonic acid.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…One of the most promising and selective strategies might be to scavenge these γKA with amine containing compounds that are more reactive than lysyl groups. Previous observations suggested that PM was a good candidate for a γKA scavenger because it reacts with γKAs about 2,000 times faster than does lysine (29). Our present study showed that PM significantly inhibited the formation of lysylIsoK adducts when coincubated with excess lysine and oxidized arachidonic acid.…”
Section: Discussionsupporting
confidence: 63%
“…118-120 °C; MS m/z 239 (M + 1), 222 (M -NH 2 ), 151 (222 -C 5 H 11 ), 136 (151 -CH 3 ). To determine the second order rate constant for pyrrole formation with a model γKA, 4-oxo-pentanal, 1 mM each of 4-oxo-pentanal and PPM, PM, or SA were incubated together and measurements carried out as described in (29) except that the reaction buffer was 50 mM phosphate buffer in 1:1 acetonitrile-water.…”
Section: Synthesis Of 5′-o-pentylpyridoxamine (Ppm)mentioning
confidence: 99%
See 3 more Smart Citations